A paradox between preoperative overweight/obesity and change in weight during postoperative chemotherapy and its relationship to survival in stage Ⅱ and Ⅲ colorectal cancer patients. Issue 4 (April 2021) - Hu, Chunlei; Zhang, Qi; Jin, Xinghan; Zhang, Lin; Zhang, Yiming; Zhu, Qiankun; Tang, Meng; Lyv, Guoqing; Shi, Hanping
Summary: Background & aims: The roles of obesity and weight management in colorectal cancer (CRC) recurrence and survival have gained a considerable amount of attention. However, whether a change in weight affects the risk of recurrence and death remains unclear. Methods: A retrospective study was conducted using Kaplan–Meier curves, multivariable Cox proportional hazards models, and restricted cubic splines in 902 patients with stage Ⅱ and Ⅲ CRC to investigate the impact of the preoperative BMI and change in weight during postoperative chemotherapy on disease-free survival (DFS) and overall survival (OS). Results: The lowest risk of cancer events (recurrence/metastasis and new CRC cases) and death occurred in patients who had a normal weight (BMI range from 18.5 to 23.9 kg/m 2 ) or had weight gain of < 5%; the patients who were underweight (BMI ≤ 18.5 kg/m 2 ) or overweight/obese (BMI ≥ 24.0 kg/m 2 ) and had weight loss or weight gain of ≥ 5% had a higher risk of cancer events and death. The association between preoperative BMI and the risk of cancer events and death exhibited U-shaped curves; the inflection points were at BMI = 24 kg/m 2 and BMI = 25 kg/m 2 for the risk of cancer events and death, respectively. The association between the change in weight and risk of death also exhibited a U-shaped curve, while the association between the change in weight and risk of cancer events was nearly linear. Multivariable Cox proportional hazards models showed that the preoperative BMI and change in weight played bidirectional roles in both the OS and DFS. Conclusions: An obesity paradox exists in patients with CRC, with both weight loss and excessive weight gain being detrimental. Patients with CRC may require a reasonable weight management program, and gaining < 5% of the preoperative weight might be an appropriate goal at 6 months after surgery.